On local chief executives and the practice of profession (2022)
The recent product endorsements and modeling stints by actor- tumed-mayor Franciso "Isko Moreno" Damagoso necessitated the examination of a provision of the Local Govemment Code that prohibits incumbent local chief executives from exercising any other profession. This Article aims to examine why the provision has remained unenforced notwithstanding the absoluteness of the prohibition and argues for its strict application.
Keywords: Local Government Code; Politicians & ethics